Parallels between Maximus the Confessor and Vladimir Soloviev (1853-1900) - Zacharia, Paraskevi (Dia-noesis: A Journal of Philosophy, 2024)
The philosophical thought of Vladimir Soloviev (1853-1900) does not appear to significantly abstain from the wholeness of humanity and the deification of human being that Maximus synthesises. In Maximus’ writings Christology is strongly bounded to love, under the soteriological meaning of Christ’s Incarnation. In Soloviev’s philosophical thought love plays the role of the cosmic power which, by transcending the historical process, leads the humanity to the deification. This paper aims at the exegesis of the three-fold nature of love (love for one’s brothers, and self-love) in Maximus’ works, while discussing the points of convergence with Soloviev’s ontology of love in Smysl lyubvi (The Meaning of Love) (1892-1894).